Computational Analysis Reveals the Characteristics of Immune Cells in Glomerular and Tubulointerstitial Compartments in IgA Nephropathy Patients - Li, Bin; Li, Suchun; Fan, Yuting; Diao, Hui; Ye, Siyang; Peng, Huajing; Chen, Wei (Frontiers in Genetics, 2022)
Objective: The commonalities and differences regarding immune states between glomerular and tubulointerstitial compartments of IgA nephropathy (IgAN) remains largely undetermined. We aim to perform bioinformatics analysis for providing a comprehensive insight toward the characteristics of immune cells and associated molecular mechanisms in IgAN. Materials and methods: We performed an integrated bioinformatic analyses by using IgAN-related datasets from the Gene Expression Omnibus database. First, the differentially expressed genes (DEGs) were identified and subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. Then CIBERSORT was employed to determine the landscape of infiltrating immune cells in both glomerular and tubulointerstitial compartments of IgAN patients, followed by Pearson correlation analysis and principal component analysis (PCA). Finally, common-shared DEGs between glomerular and tubulointerstitial entities were recognized, followed by correlation analyses to identify the dominant common-shared DEGs associated with immune cells infiltration in IgAN. Results: GO and KEGG enrichment analyses showed apparently distinct biological processes in the glomerular and tubulointerstitial compartments of IgAN. Besides, CIBERSORT analyses revealed a clear trend of increasing proportions of M1 macrophage and M2 macrophage in the glomerular compartment, while noticeably higher proportions of resting CD4+ memory T cells and M2 macrophages in the tubulointerstitial compartments. The PCA analyses showed that the varying composition of immune cells in both glomerular and tubulointerstitial entities was compelling to distinguish IgAN patients from healthy living controls. Additionally, 21 common-shared DEGs between glomerular and tubulointerstitial entities were recognized as key regulators in the pathogenesis of IgAN, among which the enhanced hemoglobin subunit beta (HBB) gene expression was found to be positively associated with M2 macrophage in the glomerular compartment and resting CD4+ memory T cells in the tubulointerstitial compartment, respectively. Most importantly, FBJ murine osteosarcoma viral oncogene homolog B (FOSB) gene deficiency was recognized as the dominant alteration in promoting M2 macrophage infiltration in the glomerular compartment of IgAN. Conclusion: The findings from our current study for the first time reveal commonalities and differences regarding immune states between glomerular and tubulointerstitial compartments, and decode the essential role of M2 macrophages and associated molecular patterns within the microenvironments of IgAN.